2022
DOI: 10.1007/s11119-022-09934-y
|View full text |Cite
|
Sign up to set email alerts
|

How can precision farming work on a small scale? A systematic literature review

Abstract: The agri-food industry faces a great challenge due to the growing global population. When considering land scarcity, this can be solved only by a higher production efficiency. Precision agriculture (PA) provides a potential answer. Most farms, especially in developing countries, are small-scale units that have difficulties in applying precision agriculture technologies. On the basis of the systematically selected articles, major benefits and constraints were identified, and solutions were provided. Due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…DA can require large upfront investments as well as significant time to adopt and troubleshoot, which can hinder its adoption. , Therefore, DA is more often associated with large-scale operations, partially because those operations are more able to afford such technologies and systems. ,, Additionally, much of the digital agricultural technology available has been developed for larger farms, which means that tools tailored to the needs of small and medium farm enterprises may not be available …”
Section: Results: Literature Review Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…DA can require large upfront investments as well as significant time to adopt and troubleshoot, which can hinder its adoption. , Therefore, DA is more often associated with large-scale operations, partially because those operations are more able to afford such technologies and systems. ,, Additionally, much of the digital agricultural technology available has been developed for larger farms, which means that tools tailored to the needs of small and medium farm enterprises may not be available …”
Section: Results: Literature Review Findingsmentioning
confidence: 99%
“…138,145 Therefore, DA is more often associated with large-scale operations, partially because those operations are more able to afford such technologies and systems. 135,146,147 Additionally, much of the digital agricultural technology available has been developed for larger farms, which means that tools tailored to the needs of small and medium farm enterprises may not be available. 148 Additional barriers beyond the financial feasibility must be overcome before farmers adopt DA practices.…”
Section: Ivii Economic Impactsmentioning
confidence: 99%
“…These rapid climate changes radiations continue to adversely impact rice production throughout growing stages based on different abiotic factors, such as rainfall, drought, temperature, flooding, and solar [32]. Precision farming is based on the observing, measuring, and responding to the variability in crop fields for strategic management [1,5,33]. It entails applying inputs when and where needed as means of sustaining crop production.…”
Section: Existing Framework Of Smart Farming Systemsmentioning
confidence: 99%
“…Innovations and growing efficiency in agriculture play a major role in increasing the potential for food and fuel production and resolving the conflict between the multifunctional use of agricultural products [8]. Moreover, a recent review study [9] concluded that many elements of precision technologies can be applied by small scale farms typical in Kosovo.…”
Section: Literature Review 21 Introduction Of Relevant Kosovar Datamentioning
confidence: 99%